The impact of electronic waste on land and its management efforts - Rahma, Ita Nur; Kamarudin, Nur Salsabila (Universitas Nahdlatul Ulama Surabaya, 2024)
Electronic waste is waste containing Hazardous and Toxic Materials (B3). Heavy metals such as lead and cadmium can acidify the soil, reduce its quality for agriculture, and threaten microorganisms that are important for soil ecology. Descriptive method, by collecting information from various written sources to describe the impact of electronic waste on the soil in depth. Sorting of electronic waste that can be recycled from that which cannot be reused. Sorting is done based on the characteristics of each component. After sorting, electronic components are dismantled using techniques such as Desoldering to separate valuable parts. Furthermore, electronic waste is crushed into small sizes and separated based on density and magnetic properties to obtain recyclable materials. In the final stage of electronic waste management, namely the Hydrometallurgy stage where valuable metals are extracted using chemical solutions, followed by refining to produce pure metals. Electronic waste management includes sorting, desoldering, crushing, and hydrometallurgy. Implementing this management method effectively and an integrated approach with government regulations, we can create an efficient electronic waste management system.